The Effect Of Using English Song In Teaching Students' Listening Ability At The Second Grade Of Smp Swasta Satria Dharma Perbaungan - Safitri, Salamuddin Selian (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
The purpose of this study was to determine the effect of the use of English songs on the listening ability of students in Class VIII of Satria Dharma Perbaungan Private Junior High School.  This study uses quantitative research methods. This research was conducted in two research classes, namely the experimental class and the control class.  The population of class VIII SMP Private Satria Dharma Perbaungan consists of 44 students, and the sample used in this study amounted to 44 students (22 students in the experimental class and 22 in the control class).  In this study, the experimental class used songs as a medium of listening learning while the control class used the conventional method.  This research data collection technique was carried out through the following steps;  giving pre-test, implementing research actions, and giving post-test.  The test was in the form of multiple choice consisting of 10 items for the experimental group and the control group.  In collecting data, the researcher used a test to determine the students' listening ability and was conducted twice, namely pre-test and post-test.  Then, the data were analyzed using t-test. The results show that ttest = 3.60252 and ttable with df = 42 using a two-tailed test with a significance of 5% = 2,018.  It shows that the value of ttest is higher than ttable (3.60252>2.018).  In other words, Ha is accepted and H0 is rejected.  It can be concluded that the use of English songs significantly affects the listening mastery of students in Class VIII of Satria Dharma Perbaungan Private Junior High School.